2009
DOI: 10.1021/bi802151w
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of Langerin and Birbeck Granule: A Macromolecular Organization Model

Abstract: Dendritic cells, a sentinel immunity cell lineage, include different cell subsets that express various C-type lectins. For example, epidermal Langerhans cells express langerin, and some dermal dendritic cells express DC-SIGN. Langerin is a crucial component of Birbeck granules, the Langerhans cell hallmark organelle, and may have a preventive role toward HIV, by its internalization into Birbeck granules. Since langerin carbohydrate recognition domain (CRD) is crucial for HIV interaction and Birbeck granule for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 64 publications
1
84
1
2
Order By: Relevance
“…Oligomeric ECD tightly bound to the mannan-agarose column through an avidity based mechanism. Monomeric CRD, in contrast, with a low affinity for its natural ligands, did not firmly bind to the mannan-agarose column and was only delayed as previously described for other C-type lectin CRDs (48,49). However, following a prior concentration to minimize the sample volume, monomeric CRD could be separated from the flowthrough on the mannan-agarose column.…”
Section: Dc-sign Constructs Productionmentioning
confidence: 80%
“…Oligomeric ECD tightly bound to the mannan-agarose column through an avidity based mechanism. Monomeric CRD, in contrast, with a low affinity for its natural ligands, did not firmly bind to the mannan-agarose column and was only delayed as previously described for other C-type lectin CRDs (48,49). However, following a prior concentration to minimize the sample volume, monomeric CRD could be separated from the flowthrough on the mannan-agarose column.…”
Section: Dc-sign Constructs Productionmentioning
confidence: 80%
“…We showed that langerin can be expressed as a homotrimer, similar to that of the soluble extracellular domain ECD (53) and that this enhances its ability to bind HIV, with no evidence of covalent langerin binding to CD4 or CCR5. These studies guided the choice of soluble langerin homologs to test as inhibitors of HIV binding to eLCs, including the trimeric ECD and the key-binding domain, the CRD.…”
Section: Discussionmentioning
confidence: 92%
“…The mean width of the Birbeck granules was 33 nm, which corresponds to what has been observed on freshly isolated human LCs. 29 The CD1a and CD207 singlepositive, as well as double-negative, cells were consistently negative for Birbeck granules (data not shown).…”
Section: Tslp-and Tgf-b-induced Lcs Express Birbeck Granulesmentioning
confidence: 83%